THE EFFECT OF BUDGETARY PARTICIPATION TO BUDGETARY SLACK WITH ORGANIZATIONAL COMMITMENT AS MODERATING VARIABLE (Study At Hospital in Bandung) - Pamungkas, Sigit; Purwanti, Meilani; Kurniawan, Aceng; Durahman (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
Abstract.    This study is a survey of Managers in Hospitals throughout Bandung City which aims to obtain empirical evidence related to the magnitude of the influence of budgetary participation on budget gaps with organizational commitment as a moderating variable. The sample size is 38 Hospitals. The unit of analysis is the Manager who is involved in budgeting. The technique for data collection is carried out through field studies by providing questionnaires, direct communication techniques and literature studies. Furthermore, for data analysis, the interaction regression analysis is used. The results of this study conclude that budgetary participation with organizational commitment as a moderating variable together have a significant influence on the budget gap of 45.5%. Partially, the variable that has the greatest influence is budgetary participation (X1) which is 1,385 units. While the organizational commitment variable has an influence of 1,115 units and the interaction between the budgetary participation variable and the organizational commitment variable (X1 * X2) has an influence of -0.012 units on the budget gap (Y).   Abstrak.  Penelitian ini merupakan suatu survei pada Manager di Rumah Sakit Se-Kota Bandung yang memiliki tujuan guna mendapatkan bukti secara empiris terkait besarnya pengaruh partisipasi penyusunan anggaran terhadap kesenjangan anggaran dengan komitmen organisasi sebagai variabel moderating. Besarnya ukuran sampel adalah 38 Rumah Sakit. Unit analisisnya adalah Manager yang diikutsertakan dalam pembuatan anggaran. Teknik untuk pengumpulan data dilakukan melalui studi lapangan dengan memberikan kuesioner, teknik komunikasi langsung dan studi pustaka. Selanjutnya untuk analisis datanya yang dipergunakan yaitu menggunakan analisis regresi interaksi. Hasil dalam penelitian ini menyimpulkan bahwasannya partisipasi penyusunan anggaran dengan komitmen organisasi sebagai variabel moderating secara bersama-sama mempunyai pengaruh yang cukup signifikan terhadap kesenjangan anggaran sebesar 45.5%. Secara parsial variabel yang memiliki pengaruh terbesar adalah partisipasi penyusunan anggaran (X1) yaitu sebesar 1.385 satuan. Sedangkan variabel komitmen organisasi mempunyai pengaruh sebesar 1.115 satuan dan interaksi antara variabel partisipasi penyusunan anggaran dengan variabel komitmen organisasi (X1*X2) mempunyai pengaruh sebesar -0.012 satuan terhadap kesenjangan anggarannya (Y).